PENANAMAN MINAT BACA MELALUI GERAKAN LITERASI SEKOLAH DI SDN SAJIRA 2 - Encep Andriana; Odin Rosidin; Rina Yuliana; Siti Lulu Maptuhah (LPPM Universitas Bina Bangsa, 2023)
This research was conducted at SDN Sajira 2 based on data of the low interest in reading at Indonesia, especially in SDN Sajira 2 School environment. This study aims to determine the implementation of the school literacy movement in instilling students’ interest at SDN Sajira 2 also to find out about teacher activities in instilling students’ interest in reading through the school literacy movement at SDN Sajira 2. This research was conducted using descriptive qualitative research methods, with descriptive research procedures, data reduction, and selection. The main data in qualitative research are words and he data source comes from primary and secondary data sources, the data collection techniques that the researcher uses are observation, interview, and documentation techniques. The data obtained os then re-examined through data reduction, than presented and concluded, after that, data will be checked for validityusing source triangulation and technical triangulation. The research at this time will describe the cultivation of reading activities for fifteen minutes before studying